Persepsi Pengguna Terhadap Inovasi Pelayanan Publik Pemerintah Provinsi Jawa Barat Melalui Aplikasi Sapawarga - Kamil, Dinda Nur Griya; Mulyana, Deddy (Anthronomics: Jurnal Manajemen Sumber Daya Manusia, 2025)
Given West Java's large population, the provincial government is compelled to pursue innovative approaches in delivering better public service. The Sapawarga application represents a key initiative by the West Java Provincial Government to meet this need, establishing a digital channel to provide services and engage with its citizens. This research objective is to analyse the user perceptions of and experiences with the Sapawarga application, evaluating its effectiveness as a digital public service innovation. Adopting a qualitative case study methodology grounded in Everett M. Rogers' Diffusion of Innovation theory, the study gathered data through in-depth interviews with the application's active users. The findings reveal that perceived usefulness and ease of use are the main factors driving the application's adoption. However, a significant barrier persists in the form of delayed responses from the provincial government to user-submitted complaints and reports. Consequently, while the integration of the Sapawarga application into public service represents a positive development according to the principles of innovation diffusion, there remains considerable scope for enhancement, particularly in backend responsiveness